Study of Grid Connected Wind Energy System with Fuzzy Logic Based MPPT Controller - Jayalakshmi N. S; Sachin S (Institute of Advanced Engineering and Science, 2018)
Renewable energy sources (RESs) are gaining more importance due to depleting fossil fuel sources in few decades. When compared to other RESs wind energy system is widely available and user friendly in nature. This paper presents modelling and simulation of grid connected PMSG based wind energy conversion system with P&O maximum power point tracking (MPPT) control technique. The PQ controller is used for grid tied inverter to exchange real and reactive power with DC bus voltage regulation. The fuzzy logic controller (FLC) is used for MPPT implementation as it provides better performance as compared to the traditional PID controllers. The various case studies are considered for power management between wind system and the utility grid and the results are evaluated in MATLAB/ Simulink platform.